Awareness regarding raised blood pressure among adult population of an urban area of Puducherry - N., Murugan; Mishra, Amit Kumar; Chauhan, Ramesh Chand; M., Mani; A., Velavan (International Journal Of Community Medicine And Public Health, 2018)
Background: Many people with high blood pressure in developing countries are not aware of their blood pressure status. This study was done to assess the awareness regarding hypertension among urban residents of Puducherry. Methods: This community based cross-sectional study was conducted in an urban area of Puducherry. All selected household were visited and the available subjects at that time were interviewed. Blood pressure was measured by using OMRON digital automatic blood pressure monitor. Descriptive statistics used to characteristic the distribution of the study respondents. Results: Among a total of 569 participants, 25.3% were hypertensive. The prevalence of hypertension was almost equal among male (26.4%) and female (24.1%). Among 144 study participants with hypertension, 74 (51.4%) were aware of their raised blood pressure whereas 70 (48.6%) were identified first time as hypertensive during the study. Majority (87.3%) of study participants responded that they were aware of a condition known as raised blood pressure, although 27.6% participants reported that their blood pressure was never measured by a doctor. Conclusions: Almost one-fourth of study population was hypertensive and the awareness regarding the same was not satisfactory.